PENGARUH PENGGUNAAN LEAFLET DENGAN SLOGAN ASSERTIF TERHADAP KEPATUHAN MINUM OBAT DAN MOTIVASI SEMBUH PADA PENDERITA TUBERKULOSIS - Herry Prasetyo; Petrus Nugroho DS; Ulfah Agus Sukrillah (Kesmas Indonesia, 2013)
ABSTRACT The main problem in curing the patient with tuberculosis is pulling out from the medication schedule. The implication of retiring the treatment is spread out the disease towards other people especialy to family member. The goal of this research is to investigate the effect of using assertive leaflet towards the obedience consuming the drugs and motivation of recovering from tuberculosis. Moreover, the benefit of this research is to obtain the empirical data about using jingle assertive on the leaflet as remembering to consum drugs and having motivation to recover from tuberculosis. As a result, this study will support the successful of PMO program by inovatif action in curing patients with tuberculosis such as mental support and increasing motivation to recover from the ilness. The research design is quasy experiment. Pre and post test with control group design was used in this research., whereas it was measuring the differences between before anf after the intervention compare to the control group.The result of the research shows that there was a significant results in the intervention group group before and after using assertive leaflet towards the obedience consuming the drugs whereas p value 0,008<0,05, on the other hand there was no change before and after in the control group. Moreover, in term of motivation of recovering from tuberculosis, the intervention group has p value 0,007 < 0,05, It means that there was a significant improvement in motivation before and after using assertive leaflet. The control group was no different in term of motivation to recover from tuberculosis pre and post test. Key words: Tuberculosis, leaflet aassertive, the obediance consuming the drugs, motivation of recovering. Kesmasindo, Volume 6, ( 1) Januari 2013, Hal. 54-63